2011
DOI: 10.1007/s00296-011-1883-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of tumor necrosis factor alpha-308 promoter polymorphism with spondyloarthritides patients in Colombia

Abstract: The pathogenesis of SpA is considered to be a complex and multi-factorial process and, similar to other autoimmune diseases, includes the activity of proinflammatory cytokines such as TNF alpha. Our study compared the -308 promoter polymorphism of TNF alpha with TNF alpha levels, HLA-B27 status, age at the onset of symptoms, SpA subtype and the clinical degree of activity in Colombian SpA patients and healthy subjects (HS). Comparisons of the TNF alpha-308A genotype among HS and SpA patients (P = 0.004), uSpA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…Our analysis showed that the TNF -308 GA/AA genotype was associated with the development of overall SpA and AS, independent of gender and HLA-B27 allelic group. This finding is in agreement with that of Höhler et al who demonstrated an association of the TNF -308 A/A genotype with AS in German patients [ 29 ] and that of Romero-Sánchez et al who showed that the A allele frequency of TNF -308 was increased in Columbian patients with SpA, AS, and rheumatoid arthritis [ 30 ]. This suggests that TNF -308A could be a susceptibility factor for this disease.…”
Section: Discussionsupporting
confidence: 92%
“…Our analysis showed that the TNF -308 GA/AA genotype was associated with the development of overall SpA and AS, independent of gender and HLA-B27 allelic group. This finding is in agreement with that of Höhler et al who demonstrated an association of the TNF -308 A/A genotype with AS in German patients [ 29 ] and that of Romero-Sánchez et al who showed that the A allele frequency of TNF -308 was increased in Columbian patients with SpA, AS, and rheumatoid arthritis [ 30 ]. This suggests that TNF -308A could be a susceptibility factor for this disease.…”
Section: Discussionsupporting
confidence: 92%
“…The TNF-a protein is a potent proinflammatory cytokine and immune modulator of joint destruction, and TNF-a possibly should be considered as a risk factor for the development of SpA and IBD [11]. TNF-a stimulates the expression of adhesion molecules and increases neutrophil activation.…”
Section: Discussionmentioning
confidence: 99%
“…and severity of SpA and IBD, as well as the response of anti-TNF treatment [3,[9][10][11][12][13][14][15][16][17][18][19][20][21]. Among the SNPs, there are two common polymorphisms that have been studied extensively.…”
Section: Research Articlementioning
confidence: 99%
“…Three single nucleotide polymorphisms (SNPs) in genes that encode inflammatory cytokines have been associated with AS, in a previous study by our research group (TNF rs1800629, IL17A rs2275913, and IL17F rs763780) (6). These polymorphisms can interfere with the level of production of these cytokines and contribute to the development of AS (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 95%